Multi-planar amorphous silicon photonics with compact interplanar couplers, cross talk mitigation, and low crossing loss - Jeff Chiles (APL Photonics, 2017)
We propose and experimentally demonstrate a photonic routing architecture that can efficiently utilize the space of multi-plane (3D) photonic integration. A wafer with three planes of amorphous silicon waveguides was fabricated and characterized, demonstrating